Supervisi Akademik Pengawas dalam Meningkatkan Kualitas Guru di Madrasah Tsanawiyah Yayasan Pendidikan Islam Badan Koordinasi Agama Islam Sei Karang - Sholeha, Dini; Hadijaya, Yusuf (Jurnal Ilmiah Global Education, 2025)
Academic supervision is a form of professional guidance provided by a supervisor to teachers with the aim of enhancing their competencies, thereby enabling them to conduct more effective and high-quality learning processes. This study seeks to explore: (1) the planning of academic supervision designed by madrasah supervisors, (2) the implementation of academic supervision by the supervisors, and (3) the follow-up actions taken after the academic supervision process. The research employs a descriptive method with a qualitative approach. Data collection techniques include observation, interviews, and document analysis. The sources of data consist of both primary and secondary data, with research subjects comprising supervisors, school principals, and teachers at MTs YAPI BKAI. The data analysis process involves data reduction, data presentation, and drawing conclusions. The findings reveal that: (1) the planning of academic supervision by the supervisors aligns with established procedures and involves the school principals in its formulation; (2) the implementation of academic supervision is effective in terms of both the techniques used and the execution process, with supervisors actively contributing to teacher development; (3) the follow-up actions taken after supervision assist teachers in addressing instructional challenges. As an indirect follow-up, it is recommended to organize relevant training programs aimed at improving teacher competencies and addressing their specific professional development needs.